A case report of pedigree of a homozygous mutation of the steroidogenic acute regulatory protein causing lipoid congenital adrenal hyperplasia. Issue 21 (May 2017) - Fu, Rong; Lu, Lin; Jiang, Jun; Nie, Min; Wang, Xiaojing; Lu, Zhaolin
Abstract: Rationale: Lipoid congenital adrenal hyperplasia (LCAH) is extremely rare, but is the most fatal form of congenital adrenal hyperplasia resulting from mutations in the steroidogenic acute regulatory protein (STAR) gene. LCAH arises from severe defects in the conversion of cholesterol to pregnenolone, the precursor of all steroids. Patient concerns: A case was reported that an 11-month-old Chinese girl who presented with a sex development disorder and hyponatremia. The clinical and genetic tests were carried out to confirm the diagnosis. The genogram of this case was also explored and analyzed. The girl presented with hyponatremia, decreased cortisol level, elevated adrenocorticotropic hormone level and female vulva despite a 46, XY karyotype. Enlarged adrenal glands and testicular-like tissue in the bilateral inguinal regions were detected with abdominal ultrasound. She was suspected of having LCAH, and definitive diagnosis was made after Sanger sequencing detected a homozygous frameshift variant c.707_708delins CTT (p.Lys236Thrfs*47) on exon 6 of the STAR gene. Diagnoses: LCAH. Interventions: She was prescribed hydrocortisone 10 to 12 mg/m2 and 9a- fludrocortisone 100 mg/d. Outcomes: Her skin hyperpigmentation and vomiting disappeared, and she had normal growth and development without adrenal crisis attacks. Her hormone and electrolyte levels remained normal, except for a persistently elevated ACTH level throughout 2 years of follow-up. At follow-up for 2 years, the patient is now 104.5 cm tall and weighs 23.3 kg at the age of 4 years old. Her plasma sodium and potassium concentration were normal. Her ACTH level is still elevated (1176 pg/mL). Her baseline sex hormone levels are testosterone <0.1 ng/dL and progesterone <0.08 ng/dL. The level of PRA (1.06 ng/mL per h) is within normal range. Lessons: This mutation was in accordance with previously reported gene mutations. The patient's parents were nonconsanguineous; her parents, paternal grandfather, and maternal grandmother were all found to be carriers of a STAR gene mutation. This 46 XY disorders of sex development case presented with adrenal insufficiency and female phenotype initially. The diagnosis was complicated depending on the clinical hormone workup. LCAH was confirmed by genetic tests and genogram of the family.